2016
DOI: 10.1016/j.sleep.2015.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Zolpidem use and motor vehicle collisions in older drivers

Abstract: Background/Objectives Prescription sleep medication use is most prevalent among women and older adults. Morning drowsiness and impaired coordination are side-effects of sleep medications that may affect driving safety. The association between current use of zolpidem-containing medications and motor vehicle collisions (MVCs) was evaluated among very old drivers. Patients/Methods Participants were current drivers aged ≥70 years residing in north-central Alabama, spoke English, had a valid driver's license, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…The epidemiologic association made between Z-drugs and motor vehicle accidents is less robust than with the benzodiazepines yet is still significant enough to warrant concern among clinicians, public health researchers, and policy makers. Studies of differing methodologies and sample populations have reported overall risk/odds ratios ranging from a 38% increased risk/odds to over double the risk/odds of traffic accidents in zolpidem users over non-users [ 24 27 ]. Despite the compelling experimental evidence for driving impairment, the epidemiological evidence for zopiclone in vehicle accidents is less clear, as some studies have found an association [ 28 , 29 ] and others have not [ 27 ].…”
Section: Motor Vehicle Accidentsmentioning
confidence: 99%
“…The epidemiologic association made between Z-drugs and motor vehicle accidents is less robust than with the benzodiazepines yet is still significant enough to warrant concern among clinicians, public health researchers, and policy makers. Studies of differing methodologies and sample populations have reported overall risk/odds ratios ranging from a 38% increased risk/odds to over double the risk/odds of traffic accidents in zolpidem users over non-users [ 24 27 ]. Despite the compelling experimental evidence for driving impairment, the epidemiological evidence for zopiclone in vehicle accidents is less clear, as some studies have found an association [ 28 , 29 ] and others have not [ 27 ].…”
Section: Motor Vehicle Accidentsmentioning
confidence: 99%
“…Another study evaluating the association between current zolpidem use and motor vehicle collision rates demonstrated that zolpidem users, especially women and drivers older than 80 years, showed higher crash rates than non-users [33]. A double-blind, balanced, cross-over driving simulator study by Bocca et al demonstrated significant residual effects on driving ability after a single nighttime intake of zopiclone and zolpidem in middle-aged drivers (55-65 years) [34].…”
Section: Driving and Pharmacotherapymentioning
confidence: 99%
“…Neuropsychiatric abnormal behaviors and symptoms, such as depression, anxiety and suicide have been reported in numerous studies [1,13,17,38]. Insomnia itself is an adverse event, but very dangerous physical and mental changes caused by sleeping pills have also been reported [2,4,15,16,19,25,29,33]. Drinking tea made from passion flowers, particularly Passiflora incarnata, has long been known to provide stability and induce sleep [22].…”
Section: Discussionmentioning
confidence: 99%
“…This is why it is known that sleeping pills are reported to have the above mentioned side effects. Many side effects of prescription sleeping pills have been reported according to the recent studies, which demonstrated that patients who suffering from irregular sleeping have possibility about metabolic disorders in bodies according to the studies [2,19,21]. In particularly, overdose and long-term intakes of sleeping pills are shown abnormal behavior during the sleep, and have reported high mortality rate of insomniac patients [19,21,29].…”
Section: Introductionmentioning
confidence: 99%